Labor courts, nomination bias, and unemployment in Germany - Helge Berger; Michael Neugart (Center for Economic Studies and ifo Institute (CESifo), 2006)
Labor courts play an important role in determining the effective level of labor market regulation in Germany, but their application of law may not be even-handed. Based on a simple theoretical model and a new panel data set, we identify a nomination bias in labor court activity - that is, court activity varies systematically with the political leaning of the government that has appointed judges. In an extension, we find a significant positive relation between labor court activity and unemployment, even after controlling for the endogeneity of court activity. The results have potentially important policy implications regarding the independence of the judiciary and labor market reforms.
Keywords: J53; K31; K41; E24; 330